Production of High Viscosity Chitosan from Biologically Purified Chitin Isolated by Microbial Fermentation and Deproteinization. (23rd April 2014) - Ploydee, Ekkalak; Chaiyanan, Saipin
Abstract : The objective of this study was to produce high viscosity chitosan from shrimp chitin prepared by using a two-step biological treatment process: decalcification and deproteinization. Glucose was fermented with Lactobacillus pentosus L7 to lactic acid. At a pH of 3.9 ± 0.1, the calcium carbonate of the shells was solubilized in 48 hours. The amounts of residual calcium in the form of ash (1.4 ± 0.5 % ) and crude protein (23.2 ± 2.5 % ) were further eliminated by the activity of proteolytic Bacillus thuringiensis SA. After decalcification and deproteinization of the shrimp shells, residual calcium and crude protein of shrimp chitin flakes were 1.7 ± 0.4 % and 3.8 ± 1.3 %, respectively. Chitin was deacetylated with 50% NaOH at 121°C for 5 hours. After deacetylation, the chitosan had residual calcium, crude protein content, and degree of acetylation of 1.6 ± 0.6 %, 0.4 ± 0.3 %, and 83.2 ± 1.5 %, respectively. The viscosity of chitosan prepared from chitin extracted by this two-step biological process was 1, 007 ± 14.7 m P a · s, whereas chitosan prepared from chemically processed chitin had a viscosity of 323 ± 15.6 m P a · s, indicating that biologically purified chitin gave chitosan with a high quality.